Four Essays on Giant Natural Resource Discoveries, Sovereign Debt Ratings, and Intergenerational Mobility - (:unkn) unknown (My University, 2023)
This thesis aims to study giant natural resource discoveries’ macroeconomic and microeconomic impacts. From a macroeconomic perspective, it analyzes the differential effects of giant discoveries on the access to international financial markets as measured by sovereign debt ratings in developing and emerging countries. Chapter 1 uses a sample of 28 developing and emerging countries and employs an ordered random effects Probit model from 1990-2014. It analyzes the impact of giant oil, gas, and mineral discoveries on short- and long-term sovereign debt ratings. It finds that discoveries have a positive or negative effect on ratings. These heterogeneous effects depend on the behavior of several macroeconomic variables and policy indicators, including tax revenues, government debt, financial market development, investment, and institutional quality. Chapter 2 studies the impact of the peak of giant resource discoveries on the Institutional Investor's Country Credit Rating (ICR) using the Synthetic Control Method (SCM). It considers five developing countries and covers the period 1985-2014. This chapter confirms the heterogeneous effects of natural resource discoveries on country ratings. The case studies reveal that factors such as diversification, sound macroeconomic and borrowing policies, strong governance, transparent resource management, adequate investment in public goods and infrastructure, and an improved business climate play an important role in making natural resource discoveries beneficial to countries. From a microeconomic perspective, it focuses exclusively on Africa and studies the microeconomic effects of mineral discoveries and productions on intergenerational mobility (IM) in education and occupation. Chapter 3 uses a dataset of 14 million individuals in 28 African countries and 2890 districts and examines the relationship between mining activities and IM in education. Using a Generalized Difference-In-Differences empirical model, it fin
Keywords: African Research